An Analysis of a Novel, Short-Term Therapeutic Psychoeducational Program for Children and Adolescents with Chronic Neurological Illness and Their Parents; Feasibility and Efficacy - Joo, Bonglim; Lee, Young-Mock; Kim, Heung Dong; Eom, Soyong (Frontiers in Neuroscience, 2017)
The purpose of this intervention was to develop a therapeutic psycho-educational program that improves quality of life in children and adolescents who are experiencing chronic neurological illness, including epilepsy, and their parents, and to analyze the intervention’s feasibility and efficacy and participants’ satisfaction. Participants were eight children(n=8) and adolescents and their parents; participating children were experiencing chronic neurological illness with psychological comorbidity; children with intellectual impairment were excluded (IQ < 80). The program was carried out weekly for four sessions. In each of the four weeks, children’s session content addressed self, emotion, coping skills, and finishing up, respectively; and parents’ session content targeted family dynamic and emotional intervention, coping skills, childcare and education, and finishing up, respectively. Clinical psychologists administered psychological assessments (viz., Child Behavior Checklist, Pediatric Quality of Life Inventory, Parenting Stress Index, Beck Depression Inventory, Children’s Depression Inventory, and Revised Children’s Manifest Anxiety Scale) at pre- and post-intervention, and administered satisfaction surveys following the intervention. Participants’ opinions about the program’s necessity, contents, and process, and participants’ overall program satisfaction were analyzed. Parents and children reported high levels of satisfaction with the program. Externalizing behavioral problems, anxiety/depression, and emotional functioning from quality of life showed improvement after the intervention. Although not statistically significant, total child stress trended downward from pre- to post-intervention. A four-session structured therapeutic psycho-educational program for children and adolescents with chronic neurological illness and their parents was successfully implemented, showing good compliance and high satisfaction and efficacy.